1999
DOI: 10.1002/(sici)1521-3935(19990401)200:4<768::aid-macp768>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Tailored synthesis of branched polymers with poly(tetrahydrofuran) having an azetidinium salt end group

Abstract: SUMMARY: Monofunctional poly(tetrahydrofuran), (poly(THF)), having a 1-(diphenylmethyl)azetidinium end group (1) was prepared and subjected to an ion-coupling reaction with various mono-and plurifunctional carboxylates (2a -j). Multiarmed polymers having 2, 3, 4 and 6 arms were obtained in almost pure form by repeating a simple precipitation of a THF solution of 1 into an ice-cooled aqueous solution containing an excess amount of the relevant plurifunctional carboxylates (2 c -g) as sodium salts. Another model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…5 In particular, we have utilized electrostatic interaction operating between moderately strained cyclic onium salt groups introduced as the end groups of hydrophobic macromolecules and polycarboxylate counteranions. Thus, a series of cyclic onium salt end groups, including four-and fivemembered cyclic and six-membered bicyclic ammonium salt groups as well as a five-membered cyclic sulfonium salt group, have been introduced as end groups on uniform-size polymers (telechelics) such as poly(THF), [6][7][8] polystyrene, 9 and poly(dimethylsiloxane). 10 It has been revealed that the five-membered cyclic ammonium (pyrrolidinium) salt group, such as an N-methylpyrrolidinium salt group, is of a particular interest, since it is stable to be isolated with carboxylates as counteranions at ambient condition but undergoes a ringopening reaction by the nucleophilic attack of a carboxylate counteranion at an appropriately elevated temperature to convert an ionic group into a covalent ester group.…”
Section: Introductionmentioning
confidence: 99%
“…5 In particular, we have utilized electrostatic interaction operating between moderately strained cyclic onium salt groups introduced as the end groups of hydrophobic macromolecules and polycarboxylate counteranions. Thus, a series of cyclic onium salt end groups, including four-and fivemembered cyclic and six-membered bicyclic ammonium salt groups as well as a five-membered cyclic sulfonium salt group, have been introduced as end groups on uniform-size polymers (telechelics) such as poly(THF), [6][7][8] polystyrene, 9 and poly(dimethylsiloxane). 10 It has been revealed that the five-membered cyclic ammonium (pyrrolidinium) salt group, such as an N-methylpyrrolidinium salt group, is of a particular interest, since it is stable to be isolated with carboxylates as counteranions at ambient condition but undergoes a ringopening reaction by the nucleophilic attack of a carboxylate counteranion at an appropriately elevated temperature to convert an ionic group into a covalent ester group.…”
Section: Introductionmentioning
confidence: 99%
“…A new polymer classification based on higher order polymer shapes has been termed as topological polymer chemistry . Of interest in this paper is the application of topological polymer chemistry to the field of polymer synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…A new polymer classification based on higher order polymer shapes has been termed as topological polymer chemistry. 12,13 Of interest in this paper is the application of topological polymer chemistry to the field of polymer synthesis. 14,15 Although topological polymers are finding their place in polymer science, understanding the relationship between the chemistry and resulting physical properties is still incomplete.…”
mentioning
confidence: 99%
“…Four-membered cyclic amines, i. e., azetidine and its derivatives, are known as a unique class of heterocyclic compounds [1,2] not only in pharmaceutical and biochemical research [3][4][5][6][7][8][9] but also in polymer chemistry [10,11] due to their potential ring-opening reactivity against appropriate nucleophiles in the presence of acids or alkylating reagents. Preceding studies on the polymerization of a variety of azetidines and N-alkylazetidines have revealed that the polymerization of azetidines proceeds via the initial formation of a quaternary cyclic ammonium (azetidinium) salt, followed by the propagation through the nucleophilic attack on this active species by an azetidine monomer.…”
Section: Introductionmentioning
confidence: 99%